Atroposelective Construction of Tetrasubstituted Axially Chiral Alkene Frameworks - Zou, Jia-Yu; Xu, Wan-Yi; Wang, Jie; Liu, Qi; He, Ying (Synthesis, 2024)
The construction of axially chiral alkene frameworks is currently one of hottest topics in the field of organic synthetic chemistry. Compared to traditional axially chiral molecules, such as biaryls, heterobiaryls, and anilides, the synthesis of axially chiral alkenes is far more challenging, especially for acyclic tetrasubstituted alkene analogues. In this review, we summarized the development of strategies for the synthesis of tetrasubstituted axially chiral alkene analogues, including asymmetric difunctionalization, C–H functionalization, cross-coupling, (dynamic) kinetic resolution, and asymmetric allylic substitution-isomerization.1 Introduction2 Synthesis of Cyclic Tetrasubstituted Axially Chiral Alkenes3 Synthesis of Acyclic Tetrasubstituted Axially Chiral Alkenes4 Summary and Outlook
Keywords: axial chirality; tetrasubstituted alkenes; difunctionalization; C–H functionalization; cross-coupling; kinetic resolution; asymmetric allylic substitution-isomerization